Evolution of the East German wage structure - Brüll, Eduard; Gathmann, Christina (Discussion paper, 2020)
We analyze the evolution of the wage structure in East Germany over the past two decades and compare it to West Germany. Both regions experienced a rise in wage inequality between 1995 and 2009 with wage dispersion in East Germany exceeding West Germany, esp. at the top. We also show that wage inequality is no longer rising in Germany and has even been declining in East Germany after 2009. Compositional changes of the workforce and selection along the employment margin play only a minor role as does the decline of union coverage for the rise in wage inequality. The adoption of minimum wages in selected industries, in contrast, explains all of the turnaround in East German wage inequality after 2009. Demand side changes seem to account for the rise in wage dispersion at the top.
Keywords: Graue Literatur